Using Learning Science, Environment, Technology and Society (SETS) Local Wisdom and based Colloids Teaching Material - Hairida Hairida (JETL (Journal of Education, Teaching and Learning), 2017)
The aim of this study was to investigate the effectiveness of learning using SETS and local wisdom based colloids teaching material on 10th-gradesenior high school students. Pretest-posttest control group design was used as the study method. Two classes have participated. XA class was chosen as experiment group which was taught using SETS and local wisdom based colloids teaching material, while on the other hand XB class was chosen as the control group which was taught using conventional colloids teaching material. The study showed that there were significant differences between two treatments given. Entrepreneurial passion and concept understanding of experiment group were better than the control group. Overall, students’ entrepreneurial passion was good. Therefore, learning using SETS and local wisdom based colloids teaching material was effective to improve entrepreneurial passion and concept understanding of students